Learning Innovative Methodologies To Foster Personal, Organizational and Community Empowerment through Online and Face-to-Face Community Psychology Courses - Francescato, Donata; University of Rome “La Sapienza” (2016)
This paper aims to illustrate the contextual factors that inspired some Italian community psychologists to develop three innovative intervention methodologies to foster personal, organizational and community empowerment. We also summarize several studies we conducted to explore the comparative efficacy of traditional and more innovative online teaching, in helping community psychology students master the competencies needed to carry out these three different intervention modalities. These studies showed that both face-to-face and online collaborative learning settings were effective not only in promoting students’ professional competencies, but also in enhancing their social capital and sociopolitical empowerment. Implications for a wider use of online settings to share community psychology values, principles and practices elaborated in different parts of the world are discussed.